2016
DOI: 10.1021/acs.analchem.6b01485
|View full text |Cite
|
Sign up to set email alerts
|

Flow-through Capture and in Situ Amplification Can Enable Rapid Detection of a Few Single Molecules of Nucleic Acids from Several Milliliters of Solution

Abstract: Detecting nucleic acids (NAs) at zeptomolar concentrations (few molecules per milliliter) currently requires expensive equipment and lengthy processing times to isolate and concentrate the NAs into a volume that is amenable to amplification processes, such as PCR or LAMP. Shortening the time required to concentrate NAs and integrating this procedure with amplification on-device would be invaluable to a number of analytical fields, including environmental monitoring and clinical diagnostics. Microfluidic point-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…(Kang et al, 2014;Zhang et al, 2015b) Therefore, the sp-SlipChip can potentially enable digital nucleic acid quantification and cell analysis directly from physiologically relevant body fluids. Furthermore, the sp-SlipChip might be seamlessly integrated with on-chip sample preparation methods (Mahalanabis et al, 2009;Schlappi et al, 2016) as well as with easy readout methods (Rodriguez-Manzano et al, 2016) for sample-in-answer-out total analysis in resource-limited settings.…”
Section: Resultsmentioning
confidence: 99%
“…(Kang et al, 2014;Zhang et al, 2015b) Therefore, the sp-SlipChip can potentially enable digital nucleic acid quantification and cell analysis directly from physiologically relevant body fluids. Furthermore, the sp-SlipChip might be seamlessly integrated with on-chip sample preparation methods (Mahalanabis et al, 2009;Schlappi et al, 2016) as well as with easy readout methods (Rodriguez-Manzano et al, 2016) for sample-in-answer-out total analysis in resource-limited settings.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the charge-based isolation approach for EVs ( 49 ), by which protamine precipitation of EVs is performed using protamine/polyethylene glycol in an overnight incubation at 4°C (similar to ExoQuick), we can say that our device has an advantage of providing 40-min in situ extraction of urine EV–encapsulated miRNAs (collection, 20 min; extraction, 20 min) at room temperature. Moreover, compared to the charge-based isolation approach for free nucleic acid ( 50 ), which uses chitosan polymer with amine groups that provide a positively charged surface only below pH 6.3, we can say that our device has an advantage of an assured positively charged surface at pH 6 to 8 of urine. Although the exact collection mechanism of EVs by nanowires in the present work must be rather complex, our findings indicated that the mechanically stable anchoring of nanowires anchored into PDMS during lysis buffer flow and the electrostatic collection of EVs (and, moreover, EV-free miRNAs) onto ZnO nanowires were two key mechanisms, and they will lead to realization of early disease diagnoses and timely medical checkups based on urine miRNA analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure the high quality of nucleic acid analysis performance on slip-driven microfluidic devices, the sample preparation module needs to be effective and efficient. There have been several microfluidic approaches for on-chip nucleic acid sample preparation, 67,68 and it will be interesting to see if these existing methods or any new methods can be seamlessly integrated with the slip-driven microfluidic devices.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%